2015
DOI: 10.1097/bot.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cortical Bone Drilling Induced Heat Production Among Common Drilling Tools

Abstract: Twist drills produced the smallest temperature rise among all bit types. Thermal effects should not be a reason for choosing K-wire size. The cannulated drill showed significantly higher temperatures when compared with standard drills, reaching maximal temperatures comparable with K wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…The detailed spatial distribution might be generated based on the cutting edge geometry [18], but the impact on the overall temperature of the operating area is limited. Lastly, the heat flux was independent of time since tool wear and chip build-up issues were found to be insignificant under proper operating conditions [21].…”
Section: Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed spatial distribution might be generated based on the cutting edge geometry [18], but the impact on the overall temperature of the operating area is limited. Lastly, the heat flux was independent of time since tool wear and chip build-up issues were found to be insignificant under proper operating conditions [21].…”
Section: Model Setupmentioning
confidence: 99%
“…To further validate the two averaged heat fluxes, they were compared to the single hole drilling data in our prior study [21], where drilling tools from eight repeated tests showed that the temperature changes caused by K-wire drilling at 0.5 mm from the hole margin was 48.7±4.5°C, and that by a twist drill was 35.1 ± 9.3°C. By applying the heat fluxes to a single hole 3D FEA (as shown in Fig.…”
Section: Heat Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] This can represent a sizable portion of the implant budget, especially at high-volume institutions. Many facilities treat orthopaedic drill bits as single-use items because of concerns regarding degradation of performance, breakage, and heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] This can represent a sizable portion of the implant budget, especially at high-volume institutions. 4,5,11,17,18 In a biomechanical model of orthopaedic drilling, we sought to answer several questions. 14 No clinical guidelines regarding when a bit should be discarded are currently available.…”
Section: Introductionmentioning
confidence: 99%